PENGARUH PENDEKATAN OPEN-ENDED DAN PENDEKATAN SCIENTIFIC TERHADAP KEMAMPUAN KONEKSI MATEMATIK SISWA SEKOLAH DASAR - Fadhilaturrahmi, Fadhilaturrahmi (Universitas Pendidikan Indonesia, 2017)
This study aims to see the influence of open-ended and scientific approach to improving mathematical connection ability of elementary school students. This study is a quasi experimental research, with the design used is